Healthy eating and family ties: educational practices mediated by playing, caring and educating (Research, Society and Development, 2020)
The present writing is a research, developed in the context of Early Childhood Education, with the purpose of discussing how an early childhood education institution is organized, as well as reflecting on the educational practices and eating habits of the children of that school. For the construction of this article, the fourth level room was used as an empirical field, composed of 25 children aged 5 and 6 years, belonging to social class C, of a Municipal Center for Early Childhood Education (CEMEI), located in city of Natal-RN, in the year 2017. The reflection of this study is organized based on the documentary analysis of the National Curriculum Reference of Early Childhood Education (RCNEI), of the Law of Directives and Bases of Education (LDB) Nº 9.394/96, of authors in the field of education, such as: Vigostsky, Piaget, Wallon, Freire, Morin and researchers in the field of nutrition who deal with the definition and concepts of healthy eating. Throughout the development of this investigation, two teaching projects were applied, one on healthy eating and the other on family, themes deemed necessary by the educator responsible for the class and the pedagogical coordinator. Through the application of these projects, it was possible to verify that the children felt more motivated to practice good eating habits and, in addition, it was possible to bring the family to school, in order for them to actively participate in their children's school life, an action difficult, because the understanding of a good part of the families is that the school is still configured as a place of assistance, being responsible alone for the education of the student.